Factors that lead to cheating on exams, case study, semester 6 civil engineering students in University Malaysia Sabah (UMS) / Ripka Rejun - Rejun, Ripka (2008)
Academic dishonesty especially cheating in exams has become a serious problem at colleges and university. Then, this research was conducted in order to study on factors that lead to cheating in exams. This research was specified to study on civil engineering student's semester 6 in University Malaysia Sabah (UMS). Then the factors selected that we want to study is examination hall arrangement, respondent's academic performance, time management and difficulties level. Research is done in University Malaysia Sabah (UMS) and specific among the civil engineering students semester 6. The whole student's semester 6 is the respondents in this research will represent the 158 civil engineering students from UMS. Questionnaire distributed among 52 respondents. After make data collection, data analyzed by SPSS tools. Through these findings, examination hall arrangement, time management and difficulties level of their syllabus have correlation with their cheating behavior. As what researchers found in their past research, academic performance has no correlation with their behavior cheating in exams. Finally, from these findings, hopefully administrator can take appropriate action in order to avoid this unethical behavior.